Ecological footprint of university students: Does gender matter? - M.A. Medina; A.G. Bruno (Global Journal of Environmental Science and Management)
To determine if there is a gender difference in the resource consumption activities of students in Central Mindanao University, a Philippine state university, an ecological foot printing study was conducted in August 2014. Consumption data from 380 student respondents were gathered using a survey questionnaire. A web-based software created by the Global Footprint Network was used to convert the consumption data into its equivalent ecological footprint value. Sample size was reduced to 324 (male = 162; female = 162) through a 1:1 nearest neighbor matching without replacement method for propensity score matching. Subsequently, unpaired t-test was employed for comparing the difference in ecological footprint between the male and female student respondents. Results reveal that the students’ ecological footprint is slightly lower than the national average. Furthermore, most of their ecological footprint comes from their carbon footprint. Male respondents were found to have a significantly higher ecological footprint compared to female respondents. This implies gender difference in terms of resource consumption.